Minimizing the Roots of a Racialized Social System: Ignoring Gender—Lethal Policing and Why We Must Talk More, Not Less, About Race and Gender. Issue 1 (28th December 2015) - Embrick, David G.
Abstract : This essay serves as a response to Hirschfield's (2015) article, "Lethal Policing: Making Sense of American Exceptionalism, " published in the December 2015 issue of this journal.